Potential Inhibitory Power of Edible Starch Phosphate Film of Yellow Ivory Coconut Shoots (Cocos nucifera var. eburnea) Incorporated with Chitosan-Nisin on The Growth of Patogenic Bacteria - Kurniawan, Dimas Zuhri; Zuhra, Cut Fatimah; Lenny, Sovia (Pendidikan Kimia FKIP Universitas Jambi, 2024)
Edible film can be used to package food well and improve the condition of the food, but damage to food ingredients can also occur due to bacteria, so chitosan-nisin is added as an antibacterial agent. In this research, Edible Film was made by adding 1,2,3,4 g of nisin to a 1% (w/v) chitosan solution to obtain four antibacterial agent solutions, namely 1.0% chitosan and chitosan-nisin: 0.1; 0.2; 0.3 and 0.4% (w/v), then mixed with distilled water, phosphate starch of yellow ivory coconut shoots, and sorbitol, then stirred with a magnetic stirrer, molded and dried in an oven and then tested for the antibacterial properties of the Edible film. The research results showed that Edible Film containing chitosan-nisin solution was the most potent antibacterial in inhibiting 1% chitosan solution with 0.4% nisin with the inhibition zone for each bacterium ranging between 29.9 mm, 30.6 mm. and 28.2 mm. Antibacterial activity increased with increasing concentration of chitosan-nisin solution.